Comparison of Agility, Sprint, Anaerobic Power and Aerobic Capacities of Soccer Players by Playing Positions - Çetinkaya, Erkan; Tanır, Halil; Çelebi, Binnur (Redfame Publishing, 2018)
This study was carried out to compare the agility, sprint, anaerobic power and aerobic capacities of the soccer players by their playing positions. 33 male soccer players (defenders (n=8) 20±1.73 years; midfielders (n=10) 20.09±1.97 years forwards (n=7) 20.55±1.91) with a training age of over 5 years playing in different positions in Kastamonu amateur league participated in the study voluntarily. First, Body Mass Index (BMI) values were calculated by measuring the height and weight of each player. Then, Illinois Agility Test, Yoyo Intermittent Recovery Test, 30 m. Sprint Test and Running-Based Anaerobic Sprint Test (RAST) were conducted. Statistical analysis was done with the SPSS 22.0 program. No statistically significant differences were observed between defenders, midfielder and forwards in Yoyo Test (m.), MaxVO2 (ml/kg/min.), RAST maximal power, RAST average power and RAST fatigue index (p>0.05). However, a significant difference was found between players in Illinois Test (sec.) and 30 m. Sprint Test (sec.) (p<0.05). Forwards and midfielders were more agile than defenders, and midfielders were faster than defenders. It will therefore contribute to their performance to evaluate physical and physiological needs according to playing positions as the distances players cover vary depending on their playing positions (defense, midfield and forward) along with the movements they perform on the pitch and the frequency of these movements.
Keywords: 2. Zero hunger